2016
DOI: 10.1136/medethics-2016-103404
|View full text |Cite
|
Sign up to set email alerts
|

Are positive experiences of children in non-therapeutic research justifiable research benefits?

Abstract: Our study shows that children participating in non-therapeutic research have various positive experiences while taking part. We argue that some of these justifiably could be taken into the risk-benefit analysis in certain situations or maybe even as a standard part of this analysis. This may help to increase the number of (crucial) non-therapeutic studies with children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…This study expands the limited knowledge base on participants' perceptions about HIV cure research 3,[32][33][34][35] and adds to research 36 on HIV cure researchers' perspectives on participant benefit. Consistent with the broader literature on indirect benefits, [17][18][19][20][21]37,38 and one study of four HIV cure research participants, 31 our study revealed that participants perceive substantial benefits associated with HIV cure research, despite clear understanding that the research offered to them has no direct medical benefit. Few of our interviewees mentioned risks or negative experiences related to the research, even when strongly encouraged to do so by the interviewer.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study expands the limited knowledge base on participants' perceptions about HIV cure research 3,[32][33][34][35] and adds to research 36 on HIV cure researchers' perspectives on participant benefit. Consistent with the broader literature on indirect benefits, [17][18][19][20][21]37,38 and one study of four HIV cure research participants, 31 our study revealed that participants perceive substantial benefits associated with HIV cure research, despite clear understanding that the research offered to them has no direct medical benefit. Few of our interviewees mentioned risks or negative experiences related to the research, even when strongly encouraged to do so by the interviewer.…”
Section: Discussionsupporting
confidence: 83%
“…This argument is supported by the Belmont Report 40 -an established set of ethical principles for human subjects research that encourages taking more than just medical benefits into account-as well as increasing discussion in the ethics literature about the importance of indirect or inclusion benefits. 38,[41][42][43] Our data suggest that psychological, social, behavioral, and healthcare-related benefits are commonly reported and valued by the HIV-cure research participants at the University of North Carolina at Chapel Hill. Supportive trusting relationships with study staff or access to healthcare may be just as important to participants as the altruistic motivations that they also mention.…”
Section: Discussionmentioning
confidence: 69%
“…The parents in our study, apart from direct health benefits for their child, also considered being "checked up" regularly as benefits for their children. Staphorst, Hunfeld, and van de Vathorst (2017) found similar results concerning benefit in their interview study with children. These children also had a much broader notion of benefit than direct health benefit.…”
Section: Benefit For Their Child Was the Most Important Factor In Thesupporting
confidence: 54%
“…Staphorst and colleagues argued, based on these results, that next to direct health benefit, other specific forms of benefit (learning, altruism, and fun) could also justifiably be qualified benefits of research participation. But they also argued that “getting extra attention from health care staff” is not one of those justifiable benefits that could be used in the risk–benefit analysis (Staphorst et al, 2017; Staphorst & van de Vathorst, 2015). We agree.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, anxiety during MRI scanning can be lessened by age-appropriate information for children, as well as by distraction [25], but these interventions were not part of the study protocol. Moreover, it should be kept in mind that, for at least some children, MRI scanning is not a source of stress, but actually a positive experience [14, 26, 27].…”
Section: Discussionmentioning
confidence: 99%